Analisis Kepuasan Tenaga Kesehatan terhadap SIMPUS (Sistem Informasi Manajemen Puskesmas) di Puskesmas Sibela Surakarta - Anggi Putri Aria Gita; Nella Tri Surya; Sri Nurul Kuraini (Jurnal Manajemen Kesehatan Indonesia, 2023)
The Sibela Surakarta Health Center has used the Management Information System of Health Center (SIMPUS) which is integrated in all sections as a flow of patient services starting from registration, polyclinic, laboratory, and pharmacy. During its implementation, SIMPUS at the Sibela Surakarta Health Center experienced various problems in data processing, one of which was a delay in the data input process to the computer caused by delays from program holders to SIMPUS officers or network delays. The purpose of this study was to analyze the satisfaction of health workers with SIMPUS at the Sibela Surakarta Health Center using the E-Servqual method. This research is a quantitative descriptive study with a cross-sectional research design using the E-Servqual method. The number of research subjects was 31 people, using quota sampling, and interviews with satisfaction questionnaires. Health workers were very satisfied with efficiency (gap value=0.01), not satisfied with reliability (gap value= -0.14), satisfied with compliance (gap value=0.00), very satisfied with privacy (gap value=0.02), dissatisfied with power responsive (gap value=-0.09), and dissatisfied with the contact (gap value=-0.08).Keywords: Satisfaction, Health Workers, SIMPUS.